Creation and Process of Creativity - Semab, Naseeb Ullah (sourcecoder, 2023)
It is also defined in literature as in other sciences. It is also clear from this that bringing something into existence is called creation. It is quite true that coming from non-existence into existence is called creation, means that it did not exist before. Now the question is whether existence If they did not have components. They also came into existence from nothing created before) if the components have been brought into existence. Until this question is answered satisfactorily, we cannot be satisfied about creation. We who write poetry short stories or novels and other such things and give the name of the creation. Some scholars and authors are the creators of creative activity with creative ability and creative thinking that creative ability is the act of self-expression and self-development that brings a person on the journey of mysticism. But it would be better if we refer to psychology to answer this question because what is going on inside the human being, what he thinks and why he does it, all this knowledge is related to psychology. Therefore, if the answer to creative action is given in the light of psychology, it may be satisfactory. The more obvious a person is, the more hidden he is. What is meant by hidden is the interiority of a person, and it is this interiority that has a big hand in a person's personality. The effect on his practical life is measured unconsciously.